Limited exposure to ambient ultraviolet radiation and 25‐hydroxyvitamin D levels: a systematic review3. (3rd February 2015) - Rice, S.A.; Carpenter, M.; Fityan, A.; Vearncombe, L.M.; Ardern‐Jones, M.; Jackson, A.A.; Cooper, C.; Baird, J.; Healy, E.
Abstract : What's already known about this topic? Hypovitaminosis D is common worldwide; adequate vitamin D levels are associated with improved health outcomes. Vitamin D can be obtained from the diet or through oral supplementation, or synthesized in human skin following exposure to ultraviolet radiation (UVR). Many authorities advocate that UVR exposure is essential for adequate vitamin D levels; however, UVR exposure can lead to skin cancer development, resulting in approximately 13 million skin cancers worldwide per annum. What does this study add? This study demonstrates that many healthy adults in different populations across the world can maintain adequate serum vitamin D levels despite negligible UVR exposure for several months of the year. Public health campaigns promoting a high vitamin D diet or supplements to healthy adults could positively impact the burden to the individual and the health service of inadequate vitamin D levels and could avoid the negative sequelae of UVR exposure. Summary: Vitamin D can be synthesized following exposure to ultraviolet radiation (UVR), ingested in the diet or provided through oral supplementation. The medical literature frequently states that humans obtain most of their vitamin D from sunshine and that UVR exposure is essential to maintain vitamin D levels. A systematic review was conducted to determine the requirement for UVR in maintaining adequate (> 50 nmol L −1 ) serum 25‐hydroxyvitamin D [25(OH)D] levels. Studies reporting serum 25(OH)D during situations of negligible UVR exposure were sought. Forty‐one studies (from a search yielding 42 698 articles) with a total of 4211 healthy adults met the inclusion criteria, providing 56 datasets from different population groups. Over 50% of subjects had > 50 nmol L −1 25(OH)D in 10 of 19 datasets reporting winter levels in areas with limited UVR. In addition, > 50% of subjects had adequate 25(OH)D levels in four of 12 datasets from polar regions during periods of negligible UVR, one of nine datasets documenting clothing‐related minimal UVR and two of eight datasets detailing employment‐related minimal UVR. The data demonstrate that many adults maintain adequate serum vitamin D levels despite negligible UVR exposure for several months. However, we acknowledge that preceding UVR exposure leading to vitamin D storage and delayed release may account for this maintenance of adequate serum vitamin D levels. There remains a need for further research on whether UVR exposure is required for longer‐term maintenance of adequate vitamin D levels.